A COMPREHENSIVE ANALYSIS OF GOVERNMENT INITIATIVES TO ERADICATE BONDED LABOR IN ARUNACHAL PRADESH, INDIA - Taba, Prem (International Journal of Research -GRANTHAALAYAH, 2024)
This paper investigates the historical underpinnings of bonded labor in India, particularly in Arunachal Pradesh, with a strong focus on government initiatives to combat this issue. It discusses the legislative framework, particularly the Bonded Labour System (Abolition) Act of 1976, and the subsequent efforts of the government in surveying and liberating bonded laborers in Arunachal Pradesh. The highlights the recommendations of the High-Power Committee on Bonded Labor and emphasizes the role of government actions in empowering marginalized communities, such as the Puroik community.